2015
DOI: 10.1021/acs.orglett.5b02804
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Free Approach for the Synthesis of N-Aryl Sulfoximines via Aryne Intermediate

Abstract: A metal-free and operationally simple N-arylation of NH-sulfoximines with aryne precursors is reported. Transition metal-free reaction conditions and shorter reaction times are the highlights of the present method. The mild optimized condition was also found to be suitable with enantiopure substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 45 publications
(13 reference statements)
0
26
0
Order By: Relevance
“…The reaction was tolerant of substituted benzyne intermediates and extended aryl units, giving rise to arylated products 28 and 13 , respectively. 28 Moreover, trapping of an indolyne intermediate delivered heterocycle-containing product 14 . When applied to non-aromatic, strained alkynes, the methodology provided alkenylated products in good yields and stereoselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction was tolerant of substituted benzyne intermediates and extended aryl units, giving rise to arylated products 28 and 13 , respectively. 28 Moreover, trapping of an indolyne intermediate delivered heterocycle-containing product 14 . When applied to non-aromatic, strained alkynes, the methodology provided alkenylated products in good yields and stereoselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…reported that N‐arylsulfoximines exhibited interesting physicochemical properties and in vitro characteristics [6] of great significance for drug development. Many N‐arylation substrates for NH‐sulfoximines have been identified, with examples of such substrates including aryl halides, [56] arylboronic acids, [57,58] aryl sulfonates, [59] arylsiloxanes, [60] aromatics, [65] aryl iodonium salts, [61] and others [62,63]…”
Section: Transformations Of Sulfoximinesmentioning
confidence: 99%
“…A set of metal‐free easy‐to‐operate N‐arylations of NH‐sulfoximines with benzyne precursors was reported in 2015 (Scheme 33). These N‐arylations with benzyne precursors were triggered with KF, and thus no transition metal catalyst was needed, [65] but benzyne precursors are expensive and difficult to prepare. This method could also provide chiral N‐arylsulfoximines.…”
Section: Transformations Of Sulfoximinesmentioning
confidence: 99%
“…We reasoned however, that if this limitation could be overcome, a general method could be developed for the synthesis of enantioenriched N-H sulfoximines. Since a number of methods exist for the functionalisation of these derivatives via alkylation, arylation, acylation and sulfonylation, [43][44][45][46][47][48][49][50][51][52][53][54] N-H sulfoximines are a versatile and sought-after synthetic intermediate for the synthesis of numerous sulfoximine derivatives.…”
mentioning
confidence: 99%